Ultrastructural localization of the CD68 macrophage-associated antigen in human blood neutrophils and monocytes. - Saito, N. (1991)
The ultrastructural localization of the CD68 antigen, a 110-kd intracellular glycoprotein associated with myeloid cells and with monocytes/macrophages, was investigated in human neutrophil granulocytes by postembedding immunogold staining, using monoclonal antibody KP1. The antigen was found in the primary granules of neutrophils, although not all primary granules were labeled. It was absent from the plasma membrane. In monocytes, it was also detected within cytoplasmic granules, colocalized with lysozyme and myeloperoxidase. This observation confirms and completes results obtained by immunofluorescence and other light-microscopic methods. Moreover this study shows that the CD68 epitope recognized by antibody KP1 is able to resist fixation and embedment and therefore emphasizes the value of using KP1 as a marker for this macrophage-associated molecule.